Investigation of ride-share service decisions with uncertainty and perceived risks: Case study of young adults in Cape Town, South Africa - Baufeldt, Jennifer (Department of Civil Engineering, 2025)
Ride-share services could help young adults avoid or delay car ownership by meeting the individuals' immediate demand for personalised private vehicle transportation. However, little is known about how young adults in South Africa, and specifically Cape Town, decide on rideshare service trips involving uncertainty and perceived risks (trips ‘at night', ‘alone' and ‘alone at night'). Using the Quantum Probability Theory concepts of Belief State and incompatibility, this research aims to better understand the influences of Gender (female, male), Access to a Private Vehicle (access, no access) and COVID-19 (‘before', ‘during', ‘after') in ride-share service decisions that involve personal security uncertainty and perceived risks in Cape Town. Evidence for incompatibility in decisions is explored using pre-questions of related Transport Factors (Sustainable Transport, Reliability, Road Safety, Crime). Additionally, positive framing questions, potentially affecting the Belief States, are tested using unrelated pre-questions, namely the Good Mood Questions. These investigations are explored through four experiments, via online surveys using Google Forms, distributed to the university community. The differences in willingness to engage in ride-share service trips ‘at night', ‘alone' and ‘alone at night' are most pronounced for Gender, however, differences per Access to a Private Vehicle and COVID-19 were also significant. Furthermore, ‘after COVID-19' indicated a significant drop in willingness to use ride-share services for these trips. The strongest evidence of incompatibility was found in females indicating impactful levels of uncertainty and perceived risks in their ride-share service decisions of ‘at night', ‘alone', and ‘alone at night'. However, limited evidence of positive framing effects was found using the Good Mood Questions for both females and males in the COVID-19 scenarios. Overall, the implications of these findings for ride-share service providers are that there is a need for more measures to improve personal security for females when taking trips ‘at night' or ‘alone at night'. While this research is limited by the scarcity of data from ride-share service companies, future research can expand on these findings by including more diverse population groups, especially lower-income groups, for more representative knowledge of the larger Cape Town population.